2011
DOI: 10.1177/0192623311425058
|View full text |Cite
|
Sign up to set email alerts
|

Toxico-Pathological Effects of In Ovo Inoculation of Ochratoxin A (OTA) in Chick Embryos and Subsequently in Hatched Chicks

Abstract: This study was designed to investigate the toxico-pathological effects of in ovo inoculation of ochratoxin A (OTA) in chicken embryos and subsequently in the hatching chicks. Nine hundred fertile white leghorn (WL) layer breeder eggs were divided into eight groups (A-H). Group A was maintained as untreated control, whereas group B was kept as sham control (10 mL of 0.1 M NaHCO 3 solution). Before incubation, groups C, D, E, F, G, and H were injected with 0.01, 0.03, 0.05, 0.10, 0.50, and 1.00 mg OTA/egg, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…Therefore, the increase in the allantoic fluid uric acid and creatinine levels may be due to a decrease in the glomerular filtration rate. The increase in the urea and creatinine levels may be due to nephrotoxic effects following the in-ovo inoculation of OTA (Zahoor-ul-Hassan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the increase in the allantoic fluid uric acid and creatinine levels may be due to a decrease in the glomerular filtration rate. The increase in the urea and creatinine levels may be due to nephrotoxic effects following the in-ovo inoculation of OTA (Zahoor-ul-Hassan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The most relevant toxic effect of OTA in animal cells is the production of reactive oxygen species (ROS) that leads to the inhibition of protein synthesis; lipid peroxidation and DNA damage, all resulting in OTAmediated oxidative damage (Ringot et al, 2006). Evidence for a role of oxidative damage in the toxicological mutagenic, teratogenic, embryotoxic, hepatotoxic, and nephrotoxic properties of OTA has been collected and described (Zahoor-ul-Hassan et al, 2012). Antioxidants can counteract the deleterious effects of chronic consumption or exposure to OTA confirming the link between OTA toxicity and oxidative stress (Sorrenti et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the adverse effects of AFB1 on embryo appeared in early life embryonic (Hassan et al, 2012). In many cases, researchers indicated that tetratogenic characteristics of mycotoxins could reduce hatchability by causing mandibular hypoplasia, softness and abnormality of the maxillary bone which impaired the final development of embryo (Hassan et al, 2012). One research demonstrated that breeder quails fed 4-6 ppb AFB have shown markedly decreased hatchability after 3 weeks (Howarth & Wyatt, 1976).…”
Section: Hatchability and Embryonic Mortalitymentioning
confidence: 99%
“…Ochratoxin, particularly OTA is considered as a potent carcinogen and classified in Group 2B by the International Agency for Research on Cancer (IARC, 1993) for humans. Ochratoxins are considered to be the main reason for causing a serious anomaly namely Balkan Endemic Nephropathy (BEN) in humans exposed to its dietary exposure (Zahoor-ul-Hassan et al, 2012;Solcan et al, 2015;Iftikhar et al, 2015;Ben Salah-Abbes et al, 2015). Ochratoxin A (OTA) causes adverse effects in poultry and is considered to be the most toxic mycotoxin along with aflatoxins for poultry birds.…”
Section: Introductionmentioning
confidence: 99%